Community structure of thermophilic photosynthetic microbial mats and flocs at Sembawang Hot Spring, Singapore - George, Christaline; Lim, Chloe Xue Qi; Tong, Yan; Pointing, Stephen Brian (Frontiers in Microbiology, 2023)
The Sembawang Hot Spring in Singapore lies at the foot of a major regional geological feature called the Bentong-Raub Suture Zone. Amid an extensively managed surface geothermal park, an undisturbed hot spring emerges with source water at 61oC, pH 6.8, and 1 mg/L dissolved sulfide. A small main pool at the source supported orange-green benthic flocs, whereas the outflow channel with gradually less extreme environmental stress supported extensive vivid green microbial mats. Microscopy revealed that cyanobacterial morphotypes were distinct in flocs and mats at several intervals along the environmental gradient, and we describe a spiraling pattern in the oscillatorian cyanobacteria that may reflect response to poly-extreme stress. Estimation of diversity using 16S rRNA gene sequencing revealed assemblages that were dominated by phototrophic bacteria. The most abundant taxa in flocs at 61oC/1mg/L sulfide were Roseiflexus sp. and Thermosynechococcus elongatus, whilst the mats at 45.7-55.3oC/0-0.5mg/L sulfide were dominated by Oscillatoriales cyanobacterium MTP1 and Chloroflexus sp. Occurrence of diverse chemoautotrophs and heterotrophs reflected known thermal ranges for taxa, although of note was the high abundance of thermophilic cellulolytic bacteria that likely reflected the large allochthonous leaf input. A clear shift in ASV-defined putative ecotypes occurred along the environmental stress gradient of the hot spring and overall diversity was inversely correlated to environmental stress. Significant correlations for abiotic variables with observed biotic diversity were identified for temperature, sulfide, and carbonate. A network analysis revealed three putative modules of biotic interactions that also reflected the taxonomic composition at intervals along the environmental gradient. Overall, the data indicated that three distinct microbial communities were supported within a small spatial scale along the poly-extreme environmental gradient. The findings add to the growing inventory of hot spring microbiomes and address an important biogeographic knowledge gap for the region.